WIND AND SOLAR POWER PLANTS AND CRYPTOCURRENCIES AS OBJECTS FOR INVESTMENT DURING THE RUSSIAN-UKRAINIAN WAR (INNOVATIVE ECONOMY, 2024)
Honak I.M., Slatvinska M.О., Protsyshyn V.V. WIND AND SOLAR POWER PLANTS AND CRYPTOCURRENCIES AS OBJECTS FOR INVESTMENT DURING THE RUSSIAN-UKRAINIAN WARPurpose. The aim of the article is theoretical substantiation of investment prospects in the development of wind and solar power plants and cryptocurrency as an effective investment object in the conditions of a full-scale Russian-Ukrainian war.Methodology of research. The methodological basis of economic research is the dialectical method of scientific knowledge. General scientific and special methods were used in the process of economic research, the most important of which are: abstract and logical methods – for formulating general conclusions of economic research; systematic approach – in determining the causes and factors of the impact of investing in wind and solar power plants and cryptocurrencies on the national economy. Also, the authors used the following special methods of economic research during the writing of the article: direct observation was carried out – collection of information about the value of the cryptocurrency Bitcoin on the website https://www.coingecko.com/en/coins/bitcoin in the period from 01.01.2023 to 01.11.2023; statistical methods of information processing were applied to determine the value of the Bitcoin cryptocurrency from January 1, 2023 to November 1, 2023.Findings. It was determined that after the start of the large-scale invasion of the Russian army into Ukraine on February 24, 2022, the structure of attractiveness of investment objects in Ukraine changed dramatically – when making investments in shares of national enterprises, Ukrainian domestic government loan bonds, and foreign currencies, economic losses occur, but investing in cryptocurrencies and green energy facilities has become much more attractive.  Investment investments of economic entities during 2022‒2023 in electric and wind power plants and other green energy facilities, which are due to both the significant economic effect of the introduction of "green" aggregates and the provision of energy independence for economic entities, have been analysed.It is substantiated that mining and trading of cryptocurrencies in Ukraine causes significant positive effects on both the macro and micro levels. The increase in the value of cryptocurrencies in 2023 has brought a significant economic effect for cryptocurrency miners and direct investors in cryptocurrency coins.It has been proven that the spheres of application of cryptocurrencies and green energy are intertwined and cause significant mutual economic impact. Therefore, it makes economic sense for an investor to engage in two businesses in parallel and simultaneously to ensure the maximum positive synergistic effect.It has been found that the impact of green energy and cryptocurrencies on the economy will undergo significant changes with the expansion of the spheres of use of cryptocurrencies and the expansion of the geography of the use of wind, power plants and other objects of green energy and the change in their legal regulation in the conditions of military operations, which will require reflection in further scientific economic research.Originality. The possibilities of parallel investment by economic entities in cryptocurrencies and wind and solar power plants with the possibility of achieving a positive synergistic economic effect during the full-scale Russian-Ukrainian war in 2022‒2023 are considered.Practical value. According to the authors, investing in wind and solar power plants of cryptocurrency is simultaneously advisable in order to achieve a positive synergistic economic effect during the full-scale Russian-Ukrainian war and the post-war period.Key words: investment, wind farms, solar farms, green energy, cryptocurrency market, cryptocurrency, crypto coin, Bitcoin.
Keywords: investment; wind farms; solar farms; green energy; cryptocurrency market; cryptocurrency; crypto coin; Bitcoin.